Self-inspection system for ground anchors monitoring on long-term load change. (September 2022) - Cheng, Shih-Hao; Chen, Shi-Shuenn; Yang, Kuo-Hsin
Abstract: This study proposes a newly method for inspecting the load changes of ground anchors (or call smart anchor assembly). The smart anchor operates in a similar fashion to that of the tell-tale load cell in principle. It only requires the components used in a typical anchor assembly and consists of only one extra strand as the reference strand, which is not engaged on the anchorage. For this method, when the anchor load changes, the anchorage moves and a relative displacement between the reference strand and anchorage is generated. Based on the measured relative displacement and the characteristics of ground anchor, the change in anchor load can be approximately calculated. At the same time, by the use of linear potentiometer, data logger, power supply, and data transmitter, automating the self-inspection function of load monitoring can also be achieved. The reliability of automatic load monitoring capabilities of the smart anchor was confirmed by sensing tests performed on field anchors. It would reduce maintenance costs and the engineers can contribute their expertise to value tasks. Lastly, when there's need to increase anchor loading, reference strands can also serve as restressing component. This can extend the service life of ground anchors and achieve the goal of sustainable development.